2019
DOI: 10.3390/ijerph16132371
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in Dutch Children Diagnosed with Oligodontia. A Cross-Sectional Study

Abstract: There is need to get insight into condition-specific oral health-related quality of life in Dutch children with oligodontia. Between October 2014 and March 2017, 11–17-year-old oligodontia patients were approached to join a study assessing the impact of oligodontia on condition-specific oral health-related quality of life (OHrQoL). The patients received a condition-specific OHrQoL questionnaire prior to the start of orthodontic treatment. Non-oligodontia children in the same age group, but also requiring ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 5 The prevalence of oligodontia is reported to range from 0.08% to 0.16% in various populations. 6 - 8 Previous studies on tooth agenesis have also reported that the most commonly missing teeth are the mandibular second premolars, lateral incisors, and maxillary second premolars. 2 , 4 , 5 , 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The prevalence of oligodontia is reported to range from 0.08% to 0.16% in various populations. 6 - 8 Previous studies on tooth agenesis have also reported that the most commonly missing teeth are the mandibular second premolars, lateral incisors, and maxillary second premolars. 2 , 4 , 5 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…5 The prevalence of oligodontia is reported to range from 0.08% to 0.16% in various populations. [6][7][8] Previous studies on tooth agenesis have also reported that the most commonly missing teeth are the mandibular second premolars, lateral incisors, and maxillary second premolars. 2,4,5,9 Since the non-development of tooth germs causes many esthetic and functional problems, including the misplacement of teeth, periodontal damage, or inadequate bone height in the upper and lower jaws, the diagnosis should be established without delay in such patients, and their treatment should be planned using a multidisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%